Detection of temperatures conducive to Arctic polar stratospheric clouds using CHAMP and SAC-C radio occultation data - de la Torre Juárez, M.; Marcus, S.; Dörnbrack, A.; Schrøder, T. M.; Kivi, R.; Iijima, B. A.; Hajj, G. A.; Mannucci, A. J. (Journal of Geophysical Research, 2009)
We use global positioning system radio occultation (GPSRO) data from the Challenging Mini-Satellite Payload for Geophysical Research and Application (CHAMP) and Satélite de Applicaciones Científicas-C (SAC-C) low Earth orbiting satellites to investigate the occurrence of air with temperatures cold enough to allow the formation of polar stratospheric clouds (PSCs) during four successive Arctic winters spanning 2001 to 2005. The GPSRO data are validated and compared with analysis data from the European Centre for Medium-Range Weather Forecasts using a series of criteria designed to eliminate faulty soundings but retain profiles which do not differ too strongly from the model data. We find that GPSRO is able to detect more PSC-prone temperature profiles during winters with disturbed conditions (in particular during December 2001 and 2003) than the analysis, but that the model fully captures the extent of PSC-prone air in winters with strong, cold vortices (in particular December 2002 and January 2005). Examination of detailed profiles for December 2001 shows that this difference is due to the ability of GPSRO to detect short-vertical wavelength features which may represent either localized gravity or global-scale planetary waves. Since the GPSRO data are now being directly assimilated into operational analysis systems, the benefits of the higher vertical resolution retrievals it provides should become evident in future observational studies of PSC formation and ozone loss, particularly under the disturbed conditions noted in several recent winters.